2020
DOI: 10.1007/s00392-020-01786-8
|View full text |Cite
|
Sign up to set email alerts
|

Developing and validating models to predict sudden death and pump failure death in patients with heart failure and preserved ejection fraction

Abstract: Background Sudden death (SD) and pump failure death (PFD) are leading modes of death in heart failure and preserved ejection fraction (HFpEF). Risk stratification for mode-specific death may aid in patient enrichment for new device trials in HFpEF. Methods Models were derived in 4116 patients in the Irbesartan in Heart Failure with Preserved Ejection Fraction trial (I-Preserve), using competing risks regression analysis. A series of models were built in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…A variety of studies have demonstrated that NT-proBNP has a stronger relationship with all-cause mortality and pump failure death than SCD ( 23 25 , 27 ) by showing a higher HR . Clinical models, including NT-proBNP, to predict pump failure death also showed better discrimination ability than to predict SCD ( 24 , 38 ). These findings indicate that NT-proBNP might not have a direct effect on SCD.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A variety of studies have demonstrated that NT-proBNP has a stronger relationship with all-cause mortality and pump failure death than SCD ( 23 25 , 27 ) by showing a higher HR . Clinical models, including NT-proBNP, to predict pump failure death also showed better discrimination ability than to predict SCD ( 24 , 38 ). These findings indicate that NT-proBNP might not have a direct effect on SCD.…”
Section: Discussionmentioning
confidence: 95%
“…Otherwise, it might lead to a biased result. However, most studies failed to adjust for LVEDD in their analyses ( 22 , 23 , 26 , 27 , 38 ). Furthermore, although NT-proBNP showed significant associations with SCD ( 22 , 38 ), a cause-and-effect relationship might not exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also used the I‐PRESERVE trial as the derivation cohort and adopted a competing risk regression model to predict the risk of sudden death. 9 Model performance was found to decline in the external validation of the CHARM‐Preserved trial (C‐statistic 0.68–0.69) and the TOPCAT trial (C‐statistic 0.64–0.73). Because traditional regression methods are difficult to effectively handle high‐dimensional interaction information in large data sets, this mechanistically limits the model's ability to predict complex relationships.…”
Section: Discussionmentioning
confidence: 97%
“…6 At present, traditional HF risk prediction tools have modest predictive power. [7][8][9] In recent years, machine learning (ML) technology based on data-driven decision-making has developed rapidly and demonstrated great potential in the diagnosis, classification, and prediction of HF. 10,11 Whether the effective prediction of malignant arrhythmia can be realized through ML urgently needs to be explored.…”
Section: Introductionmentioning
confidence: 99%